A Proposed Public Law for Disability Prevention and Rehabilitation in the Member States of the Gulf Cooperation Council - Abdullah I. Al-Hamdan; Yousef F. Qaryouti; Abdel Aziz M. Sartawi (Journal of Islamic Studies, 1994)
The main aim of this study was to develop a model public law for disability prevention and rehabilitation for the member states of the Gulf Cooperation Council , GCC, . The proposed legislation, including rules and regulations, will serve as a model for the GCC countries and other Arab states, in developing comprehensive legislation to protect the right of disabled persons. The rights for preventive, medical, social, educational, rehabilitation and employment services were clearly defined and specified as were administrative arrangements. Financial, resources and monitoring system were also included. For the development of the suggested legislation, the authors conducted an intensive review of literature including most of the international and regional statements and declarations proclaimed by the United Nations specialized agencies, and other governmental and non-governmental organizations.